The effect of risedronate treatment on serum osteoprotegerin and bone marker levels in postmenopausal women with osteoporosis - AKYÜZ, GÜLSEREN DERYA; AY, NADİYE PINAR; KARADAĞ SAYGI, NAİME EVRİM (TAYLOR & FRANCIS LTD, 2011)
Background. To evaluate the effect of risedronate treatment on osteoprotegerin (OPG), C-terminal cross-linking telopeptide of type 1 collagen (CTX), osteocalcin (OC), and deoxypyridinoline (DPD). Methods. Eighty postmenopausal osteoporotic patients were randomized into two groups. In first group, patients received 35 mg of risedronate once a week and calcium with vitamin D per day. In second group, patients received only calcium with vitamin D per day. Bone turnover markers were measured at baseline, 1st, 3rd and 6th month. Results. OPG levels were significantly reduced at 1st and 6th month of treatment in both groups, but no statistically significant difference was detected between groups. In the group treated with risedronate, difference in CTX level was observed at 3rd month of treatment, while a difference in DPD and OC levels were observed at 6th month of treatment. The baseline OPG levels correlated with age, menopause duration, and CTX levels. There was no correlation between OPG levels and the levels of the other markers during treatment. Conclusion. The present study showed that using risedronate in treatment of postmenopausal osteoporosis causes no specific changes in OPG levels; therefore, in contrast to some of the studies in the literature OPG may not be useful marker in monitoring of bisphosphonate.
Keywords: Osteoporosis; risedronate; osteoprotegerin; bone marker; SOLUBLE RECEPTOR ACTIVATOR; FACTOR-KAPPA-B; DISEASE-ACTIVITY; MINERAL DENSITY; PAGETS-DISEASE; LIGAND; TURNOVER; FRACTURES; THERAPY; MASS